Strategi Manajemen Program Unggulan untuk Meningkatkan Prestasi Santri (Studi Kasus TPQ Ashabul Qur’an Watesnegoro Ngoro Mojokerto) - siti amaroh; Wahyu Syafa'at; M Faruq Nazarudin; Lukmanul Hakim (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mmojokerto, 2025)
This study aims to analyze the management strategies of flagship programs implemented in TPQ Ashabul Qur’an, Watesnegoro, Ngoro, Mojokerto, to improve students' achievements. The main issue addressed is how the management of these flagship programs fosters optimal performance of students in various competitions at village, district, and regency levels. The research employs a qualitative approach with a case study method, involving interviews, observations, and document analysis. The findings reveal that the TPQ's success is supported by flagship programs such as Tahfidz Juz 30, character-based Islamic learning, and diverse extracurricular activities. Effective management strategies include intensive learning monitoring, parent involvement in the learning process, and a supportive religious environment. The implication of this study underscores the importance of strategic planning and value-based Islamic management to enhance the quality of education in TPQ.